Cynipidae (Hymenoptera, Cynipoidea) fauna of Burdur province (Türkiye) - Demi̇rel Mustafa; Tataroğlu, Musa; Katilmiş, Yusuf (Zootaxa, 2023)
Field studies were conducted between September 2020 and June 2022 to assess the gall wasp (Hymenoptera: Cynipidae) fauna of Burdur province (Southwestern Türkiye). A total of 69 species in 18 genera were recorded. Gall samples were collected from 150 samples collected in 100 different localities in the surveyed area. The identified species include three new records (Andricus melikai Pujade-Villar & Kwast, 2002; A. pseudocecconii Melika, Tavakoli & Stone, 2022; Saphonecrus undulatus (Мауr, 1872)) for the Turkish cynipid fauna. As a result of this study, 44 species of the current Turkish cynipid fauna were recorded from Burdur province for the first time. A checklist of the species and their host plants and/or host galls recorded in the study area is provided. The gall wasp richness and geomorphic-topographic structure of Burdur province is discussed.